2007
DOI: 10.1102/1470-7330.2007.0008
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of salivary gland tumours

Abstract: Imaging of salivary gland tumours is a major challenge for radiologists due to the great variety of differential diagnoses. This article gives a short overview on the anatomy of the salivary glands, the epidemiology of salivary gland tumours as well as the clinical presentation and the different imaging modalities including new magnetic resonance techniques such as diffusion-weighted magnetic resonance imaging, dynamic contrast-enhanced magnetic resonance imaging and magnetic resonance spectroscopy applied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
123
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(132 citation statements)
references
References 35 publications
(36 reference statements)
2
123
1
6
Order By: Relevance
“…These features are, in aggregate, different from those in other common primary malignant tumors of the salivary glands, including mucoepidermoid carcinoma and adenoid cystic carcinoma because these more common malignant tumors typically show heterogeneous attenuation or signal intensity with cystic change and necrosis. [17][18][19] Thus, an ill-defined or partially ill-defined mass without cystic regions or calcification and lacking necrosis is typically seen in salivary gland LEC. In our cases, salivary gland LECs could be classified into 3 morphologic types on the basis of the margin and shape.…”
Section: Discussionmentioning
confidence: 99%
“…These features are, in aggregate, different from those in other common primary malignant tumors of the salivary glands, including mucoepidermoid carcinoma and adenoid cystic carcinoma because these more common malignant tumors typically show heterogeneous attenuation or signal intensity with cystic change and necrosis. [17][18][19] Thus, an ill-defined or partially ill-defined mass without cystic regions or calcification and lacking necrosis is typically seen in salivary gland LEC. In our cases, salivary gland LECs could be classified into 3 morphologic types on the basis of the margin and shape.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,17,21,22 However, this modality results in considerable overlap between benign and malignant tumours in terms of imaging appearance. 3 Christe et al 22 recently reported that the sensitivity and the specificity of the above-mentioned MRI findings in predicting malignancy were 70% and 73%, respectively. As a result, the validity of conventional MRI in the differential diagnosis of salivary gland tumours is considered to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Among various imaging techniques, MRI is now the modality of choice for evaluation of suspected salivary gland tumours. 3,4 Owing to its superb contrast resolution and multiplanar facilities, MRI can clearly identify a tumour's exact location and extent, as well as its relationship with neighbouring structures. On the other hand, the sensitivity of conventional MRI in predicting malignancy is known to be quite low.…”
Section: The Authors Phong Dai Lam and Ami Kuribayashi Equally Contrimentioning
confidence: 99%
“…These characteristics can also be displayed in some benign tumors as well. Other characteristics of WTs include multiple and bilateral lesions, well-circumscribed partly cystic, partly solid lesions in CT or MRI and are often located in the tail of the parotid gland (Thoeny 2007). These features should not be considered specific characteristics associated with WTs, although some of them were present in both of our patients.…”
Section: Discussionmentioning
confidence: 79%
“…Low signal intensities on T2-weighted images were shown in both patients. Because these results are linked to highly cellular tumors (Okahara et al 2003), they are sometimes reported as a representative finding for parotid malignancies (Christe et al 2011); however, they are also described as a characteristic of WTs (Thoeny 2007). In Patient 2, it should be noted that the presence of a non-encapsulated tumor and high SUV from the FDG-PET indicate malignancy.…”
Section: Discussionmentioning
confidence: 96%